Nissolia ruddiae (Leguminosae, Papilionoideae) a new species from the Balsas river basin, Mexico - Cruz Durán, Ramiro; Sousa, Mario (Instituto de Ecología, A.C., 2004)
Nissolia ruddiae (Leguminosae, Papilionoideae), a new species from the Balsas river basin in the states of Guerrero, Morelos and Puebla, Mexico, is described and illustrated. It is similar to N. hintonii Sandwith, but differs in possessing fasciculate inflorescences, pubescence of scattered glandular setae, larger leaves, and smaller floral parts, different in form.